Captures of Molva molva (Linnaeus, 1758) still happen in NW Mediterranean waters - Kersting, Diego K. (Array, 2019)
The ling Molva molva is a widespread gadid in the Northeast Atlantic and one example of a poorly studied species of particular interest, being its distribution affected by climate warming. The ling supposedly occurs in the cold waters of the Northwestern Mediterranean Sea, where it used to be commonly fished, but to our best knowledge, records of M. molva after the 1990s are not availa-ble from the scientific literature. Here we report the recent capture of two individuals, one of them of considerable size, at 35 nautical miles off the coast of Castelló (Spain, NW Mediterranean).